Enhanced stable production of ethylene in photosynthetic cyanobacterium Synechococcus elongatus PCC 7942 - Veronica Carbonell; Eerika Vuorio; Eva-Mari Aro; Pauli Kallio (SPRINGER, 2022)
Ethylene is a volatile alkene which is used in large commercial scale as a precursor in plastic industry, and is currently derived from petroleum refinement. As an alternative production strategy, photoautotrophic cyanobacteria Synechocystis sp. PCC 6803 and Synechococcus elongatus PCC 7942 have beenpreviously evaluated as potential biotechnological hosts for producing ethylene directly from CO2, by the over-expression of ethylene forming enzyme (efe) from Pseudomonas syringae. This work addresses various open questions related to the use of Synechococcus as the engineering target, and demonstrates long-term ethylene production at rates reaching 140 mu L L(-1)h(-1) OD750-1 without loss of host vitality or capacity to produce ethylene. The results imply that the genetic instability observed earlier may be associated with the expression strategies, rather than efe over-expression, ethylene toxicity or the depletion of 2-oxoglutaratederived cellular precursors in Synechococcus. In context with literature, this study underlines the critical differences in expression system design in the alternative hosts, and confirms Synechococcus as a suitable parallel host for further engineering.